2008
DOI: 10.1007/s00428-008-0661-2
|View full text |Cite
|
Sign up to set email alerts
|

End-stage kidney disease: gains of chromosomes 7 and 17 and loss of Y chromosome in non-neoplastic tissue

Abstract: The aim of this study was to determine the copy number changes of chromosomes 7, 17, 3p, and Y in a non-neoplastic tubular epithelium in end-stage kidney disease (ESKD). Seventeen kidneys from 11 patients with ESKD were retrieved from the archive files. Non-neoplastic kidney tissue in these cases was examined separately. Tissues containing papillary adenomas (PA), clear (CRCC) and papillary renal cell carcinomas (PRCC), and myxoid liposarcoma (LPS) were examined using the same probes and compared with non-neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…The above findings suggest that papillary adenoma could be a precursor lesion of RCCs arising from ESRD. This possibility has been further supported by the gain of chromosome 7 and 17 and loss of Y chromosome, a specific cytogenetic change in papillary adenoma, observed even in non‐neoplastic tissues of ESRD by FISH analyses [7]. Also, a recent study reported that papillary adenomas and RCC are strongly associated and might represent a continuum of one biological process [25].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The above findings suggest that papillary adenoma could be a precursor lesion of RCCs arising from ESRD. This possibility has been further supported by the gain of chromosome 7 and 17 and loss of Y chromosome, a specific cytogenetic change in papillary adenoma, observed even in non‐neoplastic tissues of ESRD by FISH analyses [7]. Also, a recent study reported that papillary adenomas and RCC are strongly associated and might represent a continuum of one biological process [25].…”
Section: Discussionmentioning
confidence: 93%
“…Hes et al. [7] recently reported gain of chromosomes 7 and 17 and loss of the Y chromosome in non‐neoplastic tissues of ESRD by fluorescence in situ hybridization (FISH) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Atypical epithelial proliferations harbor some features of sporadic papillary RCC and therefore may represent early neoplastic lesions [10]. Even more, gains of chromosome 7 and 17 and loss of chromosome Y has been demonstrated in the hyperplasic and dysplastic tubules in non-neoplastic tissue of end-stage kidneys [11], which may contribute to the increased incidence of papillary RCCs in the patients with long-term hemodialysis. As we observed that calcium oxalate crystals were deposited in both non -neoplastic cysts and tumor, FISH for chromosome 1, 2, 7, 10, 13, and 17 were performed on both non-neoplastic renal cysts and tumor to see whether there were differences in chromosomal changes in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados están dentro del rango de porcentajes informados en la literatura (18,21,22 (17,18,20,22). Lo anterior ha permitido sugerir que la monosomía del cromosoma 17 es una alteración común en los tumores sólidos y que podría considerarse como un marcador cromosómico recurrente.…”
Section: Discussionunclassified